Yo Soy, I Am: Chicana Punk Pedagogy in a Composition Classroom - Hernández, Olivia J (My University, 2023)
This dissertation presents a case study of a translingual punk pedagogy within an intermediate composition classroom. In it, I share the construction of a composition curriculum that focuses on Chicanx authors engaging in multilingual self-expression of what Chicana literary scholar Tey Diana Rebolledo calls “yo soy, I am” literature. To explore the impact of this curriculum, I engaged in qualitative analysis of interviews, reflective writing, and creative works by five focal students from a section of an intermediate composition course taught at a university in Winter 2018. The multilingual texts selected for this curriculum varied in genres and modalities, including poetry, novels, academic scholarship by translingual scholars, drag performance, punk music, zines, children’s books, and visual art. I shared in the dissertation how students in the course built off of this reading to craft final projects that shared a diverse array of self-expression that crossed languages, modalities, genres, and ideas about what it means to be in an academic community. Through this analysis of student work, I argued that this translingual punk composition pedagogy, which centers readings and models of multilingual expression, fostered a learning space in which students from underrepresented minority identities experienced greater confidence in their expressive abilities, their rhetorical awareness, and in their own sense of belonging within an academic environment.
Thesis (Ph.D.)--University of Washington, 2023
Keywords: Chicana; Composition; Literature; Pedagogy; Translingual; Literature; Pedagogy; Latin American literature; English